Metabolismo respiratorio del microplancton en aguas de la península antártica - Montero, María F.; Arístegui, Javier (Comisión Interministerial de Ciencia y Tecnología, CICYT, 1996)
We have studied the respiration of microplankton (<200mm), measured as direct oxygen consumption and electron transport system activity, during two cruises carried out in coastal waters of the Antarctic Peninsula, in December, 1991 and January, 1993. 00th types of estimations were closely correlated. Therefore, enzymatic measurements were transformed to actual respiration rates. Carbon balances performed in surface waters (0- 100 m) of the Bransfield Strait showed that cornmunity (microplankton) respiration represented a greater loss of carbon, as previously considered in recently published carbon flow models from the area. However, these losses were not constant. The highests respiratory activities were associated with frontal areas between different water masses of the Bransfield Strait. Our results show that it is necessary to study the spatial variability of the microplankton respiration to understand the carbon cycle in coastal Antarctic waters. Hemos estudiado la respiración del microplancton (<200mm), medida como consumo directo de oxígeno y como actividad respiratoria del sistema de transporte de electrones, durante dos campañas llevadas a cabo en aguas de la Península Antártica en Diciembre, 1991 y Enero, 1993. Ambos tipos de estimaciones mostraron una buena correlación, por lo que las medidas enzimáticas pudieron ser transformadas a tasas reales de respiración. Los baiances de carbono iievados a cabo en aguas superficiaiec (6-1 GG m), en diferentes estaciones del Estrecho de Bransfield, mostraron que la respiración constituía una pérdida superior a lo que se ha venido considerando en modelos de carbono publicados recientemente sobre este área. Sin embargo, las pérdidas por respiración no eran constantes. En el Estrecho de Bransfield, las actividades respiratorias más elevadas se encontraron asociadas a las áreas de frente entre diferentes masas de agua. Nuestros resultados demuestran que es necesario estudiar la variabilidad espacial del metabolismo respiratorio del microplancton para poder ...